Caring for Elderly Parents with Dementia in Indonesia: A Maqāṣid al-Sharī'ah Approach - Herlina, Herlina; Muyasaroh, Muyasaroh; Husaini, Husaini; Bakhrum, Bakhrum; Zaimuddin, Zaimuddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This study explores the patterns of care for elderly parents during the critical period of dementia in order to ensure that their environment is prepared to accommodate any change that may occur. In individualistic societies, elderly care is often delegated to third parties. In contrast, in societies that adhere to religious teachings, caring for elderly parents is seen as not only an act of filial piety but also a form of repayment for the parents’ kindness, as outlined in the theory of maqāṣid al-sharī'ah. This study focuses on the pattern of care from the perspective of maqāṣid al-sharī'ah theory. Data were obtained from the “Herlina Herman Beroni” Sharia Family Law Consultation Institute. Data measurement and analysis were conducted using N-Vivo 12 simultaneously and repeatedly, to generate credible and transferable data. The results of the study showed that saturation and conflict often occur in the process of caring for parents with dementia, especially in the elderly, due to a lack of understanding in collaborating religious and medical knowledge when dealing with changes in the parents’ attitudes and actions. Children, family members, or caregivers are unprepared to accept the transition and changes in the elderly parents’ attitudes, which often leads to misunderstanding and/or neglect of the elderly parents. The implication is a shift in the obligation of children to care for elderly parents caused by discomfort in facing the dementia phase.